2003
DOI: 10.1046/j.1523-1755.2003.00269.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the Uromodulin gene in MCKD type 2 patients cluster in exon 4, which encodes three EGF-like domains

Abstract: We confirm the UMOD gene as the disease-causing gene for MCKD2. All three novel mutations were found in the fourth exon of UMOD, in which all mutations except one (this is located in the neighboring exon 5) published so far are located. These data point to a specific role of exon 4 encoded sequence of UMOD in the generation of the MCKD2 renal phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
62
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 24 publications
(35 reference statements)
9
62
0
1
Order By: Relevance
“…This finding later was confirmed by other groups [7][8][9][10][11][12][13][14] and recently was extended to autosomal dominant GCKD. 10 Uromodulin (also known as Tamm-Horsfall protein) was found to be accumulating in patch aggregates in all these conditions, suggesting a common pathogenesis.…”
supporting
confidence: 75%
See 3 more Smart Citations
“…This finding later was confirmed by other groups [7][8][9][10][11][12][13][14] and recently was extended to autosomal dominant GCKD. 10 Uromodulin (also known as Tamm-Horsfall protein) was found to be accumulating in patch aggregates in all these conditions, suggesting a common pathogenesis.…”
supporting
confidence: 75%
“…[7][8][9][10][11][12][13][14] UMOD mutations also were reported in a family with autosomal dominant GCKD. 10 The presence of a genetic defect in UMOD in MCKD2, FJHN, and GCKD (discussed next) showed that these 3 conditions are allelic.…”
Section: Heterogeneity Of Clinical Conditions Associated With Uromodumentioning
confidence: 99%
See 2 more Smart Citations
“…To date, over 50 UMOD mutations have been described, of which >90 % are missense mutations and >60 % affect the cysteine residues. The majority of these mutations are clustered in exons 4 and 5 and located in the N-terminal half of the protein [21][22][23][24][25]. The mutations cause significantly delayed maturation and trafficking of the mutant uromodulin, which in turn results in its retention in the ER, reduced expression at the plasma membrane, and decreased secretion into the tubular lumen [24,[26][27][28].…”
Section: Pathophysiologymentioning
confidence: 99%